Maternal mortality at a referral hospital in south western uganda: a 5 year descriptive analysis - Lugobe, Henry Mark; Boatin, Adeline A.; Asiimwe, Fiona; Karungi, Christine; Kayondo, Musa; Mukiza, Christine; Wasswa, Ssalongo; Ngonzi, Joseph; Wylie, Blair J.; Tamwesigire, Imelda (American Journal of Obstetrics & Gynecology, 2021)
Objective: To determine trends in the rates and causes of maternal mortality and describe clinical features among maternal deaths at the Mbarara Regional Referral Hospital (MRRH) in South-Western, Uganda. Study design: We performed a review of maternal deaths at MRRH between 2015-2019 with data extracted from prospective audits conducted within 24 hours of a maternal death using Uganda Ministry of Health standardized forms. Data included demographics, antenatal, intrapartum and postpartum care processes, cause and timing of death, and health system factors such as referral pathways. To assess completeness of data, we compared the number of audits available with departmental monthly maternity statistics reports. Maternal mortality ratio (MMR) was computed using data on live births from monthly reports. Descriptive statistics were presented using means and medians for continuous variables and proportions used for categorical variables. Results: There were 44,592 livebirths and 164 maternal deaths between 2015 and 2019, with a w 8918 births/year and MMR 375 per 100,000 live births. MMR ranged from 247 in 2016 to 606 in 2018 as in figure 1. Audit forms were completed for 124/164 (76%) of cases. Causes of death are presented in Figure 2. Most women were <30 years (62%), multiparous (76%) and were referred from another health facility (71%). Most (35%) of the women experienced delay one. The majority (83%) were unstable or critical on arrival: 52% had an abnormal vital sign, 25% were unconscious and 7% were dead on arrival. Most deaths (41%) occurred within 24 hours of admission. Conclusion: Facility-based MMR is high at this tertiary referral hospital. Leading causes of maternal death are consistent with global patterns, though unlike patterns in many low-income countries indirect causes are also common. Given the large proportion of referrals, clinical status on arrival and short time frame prior to death quality improvement strategies are needed to target referral pathways and immediate critical care and stabilization of women to make progress to reducing facility-based maternal mortality.
Keywords: Maternal mortality; Uganda; Clinical features